Penerapan Senam Kaki dan Modifikasi Diit dalam Pengontrolan Kadar Gula Darah melalui Metode Studi Kasus - Maria, Dely (Jurnal Kesehatan Holistic, 2019)
Changes in the pattern of diseases from infectious diseases to non-communicable diseases (PTM) are a major factor in the problem of morbidity and mortality. According to WHO (2013), 80% of DM patients come from developing countries, one of them is Indonesia. Based on the results of Riskesdas (2013) data, 5.7% in Indonesia had DM from the age of 15 years, the prevalence of DM in East Jakarta was 2.4%. Problems can arise when diabetes mellitus is not treated such as neuropathy and retinopathy. The method used is the case study method. This case study was carried out on 2 DM patients who experienced ineffectiveness of peripheral tissue perfusion, with the aim of implementing family nursing care Mrs. S and Mrs. M who had diabetes mellitus with ineffectiveness of peripheral tissue perfusion in Rw 03 Rt 02 and Rw 04 Rt 06 Pondok Kopi I Jakarta District East. This case study is carried out comprehensively through interviews with family baseline data, family structure, family functions, family expectations of family nursing care, and health care functions. Observation phase and physical examination of the environment, family stress and coping. This case study was conducted 6 times for 6 days in setting DM diit pattern and foot exercises 6 times in patients I and 8 times in patients II. As a result, in case I there was a decrease in GDS of 75 mg / dl from 250 mg / dl and case II there was a decrease in GDS of 156 mg / dl from 346 mg / dl, indicating an effect of decreased glucose levels and increased sensitivity of the feet in both cases. Keywords: Diabetes Melitus, Foot Gymnastics, Peripheral Tissue Perfusion, Diit